Disability Among Frail Elderly Patients Scheduled for Coronary Artery Bypass Graft Surgery. - Awad Attia, Marwa Mohamead; Abdallah, Eman Shokry; Elsayed Atia, Nashwa Saber (Journal of Neonatal Surgery, 2024)
Background: Preoperative identification of disability among frail elderly individuals scheduled for coronary artery bypass graft (CABG) surgery is essential for perioperative risk stratification and care planning. Aim: Assess the prevalence and level of disability among frail elderly patients prior to elective CABG surgery. Methods: A descriptive cross-sectional study was conducted on 80 elderly patients (≥60 years) scheduled for elective on-pump CABG at the Cardiothoracic Department, Sudeanie Hospital, Zagazig University Hospitals. Frailty was assessed using the Clinical Frailty Scale (CFS), and disability was measured using the 12-item World Health Organization Disability Assessment Schedule (WHODAS 2.0). Results: The mean age of participants was 69.2 ± 2.7 years; 72.5% were male. Regarding disability, 55% had mild disability, 35% moderate disability, and 3.75% severe disability. Higher education level and regular exercise were significant negative predictors of disability, whereas marital status, residence, and living arrangements were significant positive predictors. Conclusion: Mild to moderate disability is common among frail elderly patients scheduled for CABG surgery. Sociodemographic and lifestyle factors significantly influence disability levels. Recommendation:Routine preoperative frailty and disability screening should be integrated into cardiac surgical assessment to optimize perioperative management..